Bipolar disorder: an overview - Elmien Bronkhorst; Jean Motubatse (South African Family Practice)
Bipolar disorder (BD) is a chronic disorder characterised by abnormal mood changes and fluctuation in energy levels. The disease is characterised by a depressive episode, which can last up to a few months, and include low energy levels, hypersomnia, cognitive impairments, decreased sexual desire, carbohydrate craving, and weight gain. Conversely, bipolar disorder also has a stage of exhilaration and excitement, which can be classified as a manic episode. The typical presentation of these episodes of mania includes high energy hallucinations and delusions, sleep deprivation, fast speech and a constant need to be active. Risk factors that contribute to development of BD include the use of cannabis, influenza during the third trimester of pregnancy, as well as smoking during pregnancy, the use of cocaine, opioids, tranquilisers, stimulants and sedatives during pregnancy, and regular substance use during a period of a year. Parental loss before the age of five, war trauma and stress, as well as traumatic head injury may influence the condition.